1998
DOI: 10.1080/026990598122197
|View full text |Cite
|
Sign up to set email alerts
|

Female TBI patients recover better than males

Abstract: The purpose of the present study was to look at possible gender differences in outcome after severe traumatic brain injury. Three hundred and thirty four consecutive patients, 72 females and 262 males, age range 5-65 years, were included in the study. Age range and severity of injury, evaluated by duration of unconsciousness, did not differ between male and female patients. Predicted outcome at the time of discharge from an in-patient rehabilitation programme was evaluated according to work capacity. Female TB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
107
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(112 citation statements)
references
References 9 publications
4
107
1
Order By: Relevance
“…[19][20][21][22][23][24][25][26][27][28][29][30][31] However, these research findings are mixed. [19][20][21][22][23][24][25][26][27][28][29][30][31] Our study focused on the specific executive functions deficit in SA after TBI, which not been well studied with regard to gender. The study purpose was to examine (1) possible gender differences in SA of injury-related deficits and (2) possible causes for these gender differences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[19][20][21][22][23][24][25][26][27][28][29][30][31] However, these research findings are mixed. [19][20][21][22][23][24][25][26][27][28][29][30][31] Our study focused on the specific executive functions deficit in SA after TBI, which not been well studied with regard to gender. The study purpose was to examine (1) possible gender differences in SA of injury-related deficits and (2) possible causes for these gender differences.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14][15][16][17][18] Mixed findings are typical in studies comparing broad post-TBI outcomes for men and women. [19][20][21][22][23][24][25][26][27][28][29][30][31] On the one hand, research has shown that women with TBI outperform men in executive functions, 1 working memory, 27 delayed visual memory, 20 and written language, 21 as well as in rehabilitation outcomes 21 and community integration. 22,23 Investigators have also noted that women are more likely to survive their injuries and less likely to have postinjury complications than men.…”
mentioning
confidence: 99%
“…After traumatic brain injury (TBI) women have also shown better recovery than men (Groswasser et al, 1998). These reported differences between males and females could be the result of hormonal influences on outcome.…”
Section: Gendermentioning
confidence: 92%
“…There are a few studies which indicate that gender was associated with different outcomes, but those studies included a smaller number of patients after TBI. It has been shown in a few studies that the better outcomes in females might be due to the neuroprotective effect of progesterone [12]. On the other hand, several other studies indicate that females have poorer prognosis than males [13,14].…”
Section: Discussionmentioning
confidence: 93%